Macrophyte and algal studies of some lakes in the Mackenzie Delta and on the Tuktoyaktuk Peninsula, 1985-86 - Ramlal, P.S.; Anema, C.; Cummings, E.; Fee, E.J.; Guildford, S.J.; Hallard, K.; Hecky, R.E.; Hesslein, R.H.; Himmer, S.; Kling, H.; Mathew, D.; Nernberg, D.; et al. (Canada. Dept. of Fisheries and Oceans. Central and Arctic Region, 1991)
Not to be cited without permission of the issuing establishment This report is a compilation of data collected regarding distribution, abundance and growth of macrophytes, nutrient status indicators of phytoplankton, epiphyton and epipelon, photosynthesis rates of epiphyton and epipelon, and biomass and cell number estimates of phytoplankton from study lakes in the Mackenzie Delta and the Tuktoyaktuk Peninsula during the open water periods of 1985 and 1986.